2001
DOI: 10.1111/j.1741-3729.2001.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Personal Social Network as a Factor in Parent Education Effectiveness

Abstract: This study examined the impact of mothers' involvement with their social networks upon their self-reported changes in behaviors and attitudes due to a parenting intervention-in this case monthly, age-paced parenting newsletters. Path analyses revealed that discussing and sharing newsletter copies with others was associated with greater self-reported change but did not significantly mediate the relationship between newsletter use and parental change. Rather, individual use of the newsletter and social sharing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Though the response rate for this study was approximately 42 percent, it was quite comparable to response rates reported in prior newsletter research (Bogenschneider & Stone, 1997;Riley et al, 1991;Walker & Riley, 2001). There were some minor challenges in the distribution of the newsletter and collection of the questionnaires.…”
Section: Study Limitations and Future Researchsupporting
confidence: 63%
See 1 more Smart Citation
“…Though the response rate for this study was approximately 42 percent, it was quite comparable to response rates reported in prior newsletter research (Bogenschneider & Stone, 1997;Riley et al, 1991;Walker & Riley, 2001). There were some minor challenges in the distribution of the newsletter and collection of the questionnaires.…”
Section: Study Limitations and Future Researchsupporting
confidence: 63%
“…In future efforts, newsletters could be combined to include sections that specifically address both fathers and mothers. Such parenting newsletters may influence mothers, mother figures, fathers, and father figures to increase recognition, respect, and support for the importance of both roles in the growth and development of children, as well as the interactions between parents and with others (Walker & Riley, 2001).…”
Section: Study Limitations and Future Researchmentioning
confidence: 99%
“…90,99 For example, mothers' social networks may influence whether they are likely to enter and continue in an intervention. In a study examining participation in prevention programs, women with lower density networks and less frequent contact with kin were more likely to seek child-rearing advice than women in denser, more kin-involved networks.…”
Section: Social Network and Interventions Promoting Maternal Mental mentioning
confidence: 98%
“…93,94 Given the stress related to parenting, particularly in mothers from at-risk communities, there have been numerous interventions targeted toward improving parenting competence and, thus, decreasing the associated stress and strain on the mothers' emotional and mental health. 95 Although studies have addressed social networks in mental health interventions 96 and social networks and social support in parenting interventions, 71,90 there is only limited information on the role of social networks in mental health interventions specially for mothers. The importance of incorporating supportive social networks into interventions aimed at mothers is highlighted by the fact that these interventions are often conducted in groups.…”
Section: Social Network and Interventions Promoting Maternal Mental mentioning
confidence: 99%
See 1 more Smart Citation